Aligned carbon nanotubes composites for flexible pressure sensors - Sepúlveda, A. T. (2011)
Carbon nanotubes (CNTs) have been focus of considerable study and several researchers have reported notable mechanical and physical properties for this type of carbon. The exceptional electronic properties and thermal conductivity of the CNTs make them excellent candidates for the development of new material systems.